Family-Work and Private Life of Women: Qualitative Changes in the Remote Working Environment - Tonkikh, Natalia (Journal of Economic Sociology, 2023)
The article problematizes the relevance of identifying the relationships between modern remote employment opportunities for women and potential changes in their lives including reproductive plans. The hypothesis of the study is that remote employment conditions, due to their flexibility in the workplace and working time, allow most women to improve their work-life balance as well as plan their future family life. The 1 purpose of the study is to assess women’s opinions about expected or real changes in their work, family, parenthood, and personal spheres of lives in connection with possible or actual participation in remote forms of employment. The article summarizes the results of three Russian women’ surveys containing a monitoring question about the remote working conditions impact on the state of the main spheres of life (2018, N = 1922; 2019, N = 601; 2022, N = 589). Data merging was carried out using the VORTEX-10 program (N = 3112). The array is divided into three groups: (1) women with voluntary remote work experience before the pandemic; (2) women with forced remote work experience during the pandemic; (3) women without remote work experience. Women’ subgroups were additionally identified by age and the presence/absence of children under 15. The results were processed by translating the answers into a unified index system. The findings show the predominance of positive assessments of the remote employment conditions influence on the main respondents’ spheres of life: work, family, parental and personal. Respondents from different subgroups were unanimous noting the positive remote work impact on improving home life (“at home it will become more comfortable”), the health of loved ones, more time to communicate with children, as well as time for personal life, the latter manifested in the emergence of “time for myself” and “for cultural life.” At the same time, women who have voluntary remote work experience are two times more likely to evaluate its benefits for themselves than women who were forced to work remotely. Women with children under 15, compared to other respondents, more often rate the remote employment experience as positive (the difference is 25%). There is no significant connection between the ability to work remotely and plans to have children.